The Southampton Examination Schedule for the diagnosis of musculoskeletal disorders of the upper limb /La “Southampton Examination Schedule” per la diagnosi delle patologie muscolo-scheletriche dell’arto superiore - Palmer, K.T. (La Medicina del Lavoro, 2007)
Background: The optimum classification of upper limb disorders (ULDs) remains a cause of debate. Recent efforts to address the issue have focused on translating the consensus criteria of experts into workable protocols for use in field epidemiology. Objectives: This paper describes the development and assessment of one such protocol, the Southampton Examination Schedule for ULDs. Results and Conclusions: In the absence of a reliable gold standard, the schedule has so far been evaluated in terms of its repeatability within and between-observers in clinical and community settings, and in terms of its capacity to distinguish groups with different severity of disease, different treatment needs, different risk factors and different prognoses. Findings to date are briefly summarised. The most pressing future goal in this field is for researchers to collect data on the component elements of diagnosis according to common evidence-based standards such as the Southampton Schedule in order to facilitate communication, the effective pooling of data and the empirical assessment of alternative choices of case definition.La “Southampton Examination Schedule” per la diagnosi delle patologie muscolo-scheletriche dell’arto superioreLa più idonea classificazione dei disturbi dell’arto superiore rimane oggi motivo di dibattito. Recenti lavori, rivolti a tale problematica, hanno tentato di tradurre i criteri di consenso dettati dagli esperti in protocolli utilizzabili in campo epidemiologico. Questo articolo descrive lo sviluppo e la valutazione di uno di questi protocolli: “The Southampton Examination Schedule” per i disturbi dell’arto superiore. In assenza di un gold standard affidabile, la “Schedule” è stata finora valutata in termini di ripetibilità intra-osservatore e tra osservatori diversi, sia in ambito clinico che nella popolazione generale, e in termini di affidabilità nel distinguere gruppi differenti per quel che riguarda la severità della patologia, la necessità di cure, i fattori di rischio e la prognosi. I risultati finora ottenuti vengono brevemente riassunti. È indispensabile per il futuro che un obiettivo prioritario sia l’utilizzo da parte dei ricercatori di strumenti per la raccolta dei dati basati sull’evidenza, come “The Southampton Examination Schedule”, al fine di facilitare la comunicazione, di ottenere una banca dati omogenea e di valutare empiricamente possibili alternative nella definizione di caso.